Fluid Resuscitation and Blood Product Replacement in Postpartum Hemorrhage - Tiffany Moore Simas; Lyn Riza; Susan Pasquale; Robert Berry; Mark Manning; Dawn Tasillo (Association of American Medical Colleges, 2010)
Abstract This resource is a comprehensive tutorial module for intravenous fluid resuscitation and blood product replacement during the management of postpartum hemorrhage. The module was prepared for use in residencies with significant obstetrical training but is appropriate for any individual seeking detailed information on fluid and blood product resuscitation in the management of postpartum hemorrhage. It can be used in conjunction with postpartum hemorrhage simulation, in support of didactic sessions, or as a stand-alone discussion or review of the subject matter. The presentation contains a narrated PowerPoint slide set with embedded summary tables. There is a transcription of all audio narration so that the resource is usable by the hearing impaired. The module was developed as part of a comprehensive blended learning curriculum for teaching the management of postpartum hemorrhage. The full curriculum included seven online modules followed by face-to-face teaching and learning with task trainers and a multidisciplinary simulation case. Project-associated pre- and posttesting demonstrated clear improvement in mastery of material as a result of using this module. All trainees completing the module reported that the module increased their knowledge "moderately" or "to a great extent." Additionally, all trainees reported that they "agreed" or "strongly agreed" that they would recommend the module to another learner.